Right ventricular dysfunction in patients with COVID‐19 pneumonitis whose lungs are mechanically ventilated: a multicentre prospective cohort study. (24th May 2022) - McCall, P. J.; Willder, J. M.; Stanley, B. L.; Messow, C‐M.; Allan, J.; Gemmell, L.; Puxty, A.; Strachan, D.; Berry, C.; Shelley, B.G.; ,
Summary: Cardiovascular complications due to COVID‐19, such as right ventricular dysfunction, are common. The combination of acute respiratory distress syndrome, invasive mechanical ventilation, thromboembolic disease and direct myocardial injury creates conditions where right ventricular dysfunction is likely to occur. We undertook a prospective, multicentre cohort study in 10 Scottish intensive care units of patients with COVID‐19 pneumonitis whose lungs were mechanically ventilated. Right ventricular dysfunction was defined as the presence of severe right ventricular dilation and interventricular septal flattening. To explore the role of myocardial injury, high‐sensitivity troponin and N‐terminal pro B‐type natriuretic peptide plasma levels were measured in all patients. We recruited 121 patients and 118 (98%) underwent imaging. It was possible to determine the primary outcome in 112 (91%). Severe right ventricular dilation was present in 31 (28%), with interventricular septal flattening present in nine (8%). Right ventricular dysfunction (the combination of these two parameters) was present in seven (6%, 95%CI 3–13%). Thirty‐day mortality was 86% in those with right ventricular dysfunction as compared with 45% in those without (p = 0.051). Patients with right ventricular dysfunction were more likely to have: pulmonary thromboembolism (p < 0.001); higher plateau airway pressure (p = 0.048); lower dynamic compliance (p = 0.031); higher plasma N‐terminal pro B‐type natriuretic peptide levels (p = 0.006); and raised plasma troponin levels (p = 0.048). Our results demonstrate a prevalence of right ventricular dysfunction of 6%, which was associated with increased mortality (86%). Associations were also observed between right ventricular dysfunction and aetiological domains of: acute respiratory distress syndrome; ventilation; thromboembolic disease; and direct myocardial injury, implying a complex multifactorial pathophysiology.